In the Light of Evolution: Volume VI: Brain and Behavior - National Academy of Sciences
The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia–in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences–and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium \

In the Light of Evolution: Volume V: Cooperation and Conflict - National Academy of Sciences
Biodiversity–the genetic variety of life–is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia–in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences–and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium \